-16+x=x+13

Simple and best practice solution for -16+x=x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16+x=x+13 equation:


Simplifying
-16 + x = x + 13

Reorder the terms:
-16 + x = 13 + x

Add '-1x' to each side of the equation.
-16 + x + -1x = 13 + x + -1x

Combine like terms: x + -1x = 0
-16 + 0 = 13 + x + -1x
-16 = 13 + x + -1x

Combine like terms: x + -1x = 0
-16 = 13 + 0
-16 = 13

Solving
-16 = 13

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 25x^3-20x^2+5x=0 | | am^2+16m+1=0 | | b^2(b^2+8)= | | 6x+13x=76 | | 3x^3y+6x^2y^2-12x^2y=0 | | 6(3x+1)=2x-7x | | 12-4x=2x-2 | | 2.03x(1.27x-2.36)= | | -15x^5-5x^4=0 | | 9(3x+1)=4x-7x | | -x+7=28 | | 3(-2-x)= | | x(b+2)= | | 8r+9=-5.37-6 | | 1.8r+9=5.7-6 | | 9v^2+21v+18=0 | | 10b^2-23bc-5c^2= | | 9s^3+15s^2-36s= | | -2(n-7)-(9+6n)=-9n | | 6s^2-17s+12= | | -4(k+6)-(-3k-6)=-2k | | 3t^2-33t+84= | | -5+2x=5x-4 | | V^4-100= | | 7(x+5)=8x-7 | | (-3)-(-7)+8=a | | (-3)-(-7)+8=a-d | | 75r^2-192= | | (7b-3)-3(2b+4)=-6 | | w^4-64= | | 64w^2-25d^2= | | (-6)-6=a+d |

Equations solver categories